This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First note that for the terms to be real-valued we must have that
( 2 x − 1 ) ≥ 0 ⟹ x ≥ 2 1 .
Now, square both sides to find that
( x + 2 x − 1 ) + ( x − 2 x − 1 ) + 2 x 2 − ( 2 x − 1 ) = 2
⟹ 2 x + 2 ( x − 1 ) 2 = 2
⟹ 1 − x = ( x − 1 ) 2
⟹ 1 − x = ∣ x − 1 ∣ .
Now for x ≤ 1 we have that ∣ x − 1 ∣ = − ( x − 1 ) = 1 − x , so for x ≤ 1 we end up with the tautology 1 − x = 1 − x , i.e., true for any x ≤ 1 .
For x ≥ 1 we would end up with 1 − x = x − 1 ⟹ x = 1 , a solution we already know exists.
Combining this with our initial observation gives us that 2 1 ≤ x ≤ 1 .
Thus a = 1 , b = 2 , c = 1 and a + c b = 1 + 1 2 = 1 .